The Impact of Live Streaming Appeal and Discounts for Generation Z in Online Purchasing Decisions - Wahyudi, Tri Nur; Harsono, H; Elita, Via (Universitas Muhammadiyah Surakarta, 2024)
The importance of technology and the internet has revolutionized the way people shop, especially among Generation Z who show high interest in online shopping. This study aims to identify the impact of live streaming and discounted prices on the purchasing decisions of Shopee users from Generation Z in Indonesia. Using an associative quantitative method, primary data collected from 102 respondents through an online questionnaire was analyzed using SPSS for Windows. The results revealed that both live streaming and price discounts have a significant influence on the purchasing decisions of Generation Z on the Shopee platform. both simultaneously and partially with a coefficient of determination (R2) value of 0.505.